2009
DOI: 10.1086/595758
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Evolutionary Responses to Cell‐Lineage Selection on Growth Form and Its Plasticity in a Red Seaweed

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. abstract: Despite much theoretical discussion on the evolutionary significance of intraclonal genetic variation, particularly for modular organisms whose lack of germ-soma seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 76 publications
3
29
0
Order By: Relevance
“…They are multicelled sub-units, whose iteration proceeds by mitotic division from a special totipotent and immortal group of cells known as apical meristems (Tuomi and Vuorisalo 1989b;Monro and Poore 2009). A typical plant module is found at the tips of roots and shoots.…”
Section: Modularitymentioning
confidence: 99%
“…They are multicelled sub-units, whose iteration proceeds by mitotic division from a special totipotent and immortal group of cells known as apical meristems (Tuomi and Vuorisalo 1989b;Monro and Poore 2009). A typical plant module is found at the tips of roots and shoots.…”
Section: Modularitymentioning
confidence: 99%
“…Examples come from plants and colonial marine animals such as red algae (Monro and Poore 2009), sponges (Maldonado 1998), bryozoans , hydroids (Shenk and Buss 1991;Hart and Grosberg 1999), ascidians (Sommerfeldt and Bishop 1999;Ben-Shlomo et al 2001;Sommerfeldt et al 2003) and corals (Frank et al 1997; Barki et al 2002;Nozawa and Loya 2005;Amar et al 2008;Puill-Stephan et al 2009). Enhanced performance due to either increased organism size or a more diverse genetic 'repertoire' is commonly cited as a possible benefit of chimerism that could favor cooperation rather than conflict and so allow chimeric entities to persist in nature (Pineda-Krch and Lehtilä 2004; Amar et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of our experiment was to exploit the latter, based on considerable evidence of heritable variation (e.g., due to somatic mutation) arising within clonal lineages of diverse taxa during growth (Fagerström, Briscoe, & Sunnucks, 1998; Gill, Chao, Perkins, & Wolf, 1995; Whitham & Slobodchickoff, 1981). Intraclonal variation of this kind can accumulate remarkably rapidly in several groups of macroalgae (Meneses, Santelices, & Sanchez, 1999; Poore & Fagerström, 2000) and especially in fast‐growing, filamentous forms like Oedogonium (Lawton et al., 2015; Monro & Poore, 2009). Similar to our results, past efforts to select upon intraclonal variation in red macroalgae have yielded responses that were consistent among genotypes for some traits and genotype‐specific for others (Monro & Poore, 2009), suggesting that the mutational target size of traits determines the amount of variation that becomes available for selection or that genotypes/strains differ in the rate that variants accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…Intraclonal variation of this kind can accumulate remarkably rapidly in several groups of macroalgae (Meneses, Santelices, & Sanchez, 1999; Poore & Fagerström, 2000) and especially in fast‐growing, filamentous forms like Oedogonium (Lawton et al., 2015; Monro & Poore, 2009). Similar to our results, past efforts to select upon intraclonal variation in red macroalgae have yielded responses that were consistent among genotypes for some traits and genotype‐specific for others (Monro & Poore, 2009), suggesting that the mutational target size of traits determines the amount of variation that becomes available for selection or that genotypes/strains differ in the rate that variants accumulate. Nevertheless, past work has shown that clonal propagation can also generate persistent nongenetic effects on trait expression (Schwaegerle, 2005), analogous to parental effects in sexual organisms.…”
Section: Discussionmentioning
confidence: 99%